IMF Research Bulletin, September 2012. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2012)
The research summaries in the September 2012 issue of the IMF Research Bulletin are "Surges in Capital Flows: Why History Repeats Itself" (by Mahvash S. Qureshi) and "The LIC-BRIC Linkage: Growth Spillovers" (by Issouf Samake, Yongzheng Yang, and Catherine Pattillo). The Q and A covers "Seven Questions on Monetary Transmission in Low-Income Countries" (by Prachi Mishra and Peter Montiel). "Conversations with a Visiting Scholar" features an interview with IMF Fellow Olivier Coibion. Also included in this issue are details on the IMF Fellowship Program, visiting scholars at the IMF, a listing of recently published IMF Working Papers and Staff Discussion Notes, and an announcement on IMF Economic Review's first Impact Factor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet